2020
DOI: 10.1021/acsnano.0c00847
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cascade Resonance Energy Transfer in Dynamic Nanoassembly for Intensive and Long-Lasting Multicolor Chemiluminescence

Abstract: Light emission induced by chemical reactions, known as chemiluminescence (CL), has been widely used for bioassays, biosensors, imaging, and illumination applications. Most known CL systems exhibit flash-type single-color light emissions, which limit their applications. Long-lasting multicolor CL in aqueous solutions is highly desirable, especially for biological applications, but remains a challenge. Herein, we report a simple strategy of achieving highly efficient cascade Forster resonance energy transfer (FR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…Hydroxypropyl methylcellulose was utilized to slow down the diffusion rate, while the reaction was buffered by addition of solid Ca(OH) 2 . Moreover, it was found that Co 2+ -chitosan increased the CL emission of the system when merged with the β-CD nanoassembly system [126]. Another important study by Lipper et al, described that CL energy transfer from Schaap's dioxetane probe can be efficiently used for ratiometric pH imaging.…”
Section: Intermolecular Chemiluminescence Emission Modementioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxypropyl methylcellulose was utilized to slow down the diffusion rate, while the reaction was buffered by addition of solid Ca(OH) 2 . Moreover, it was found that Co 2+ -chitosan increased the CL emission of the system when merged with the β-CD nanoassembly system [126]. Another important study by Lipper et al, described that CL energy transfer from Schaap's dioxetane probe can be efficiently used for ratiometric pH imaging.…”
Section: Intermolecular Chemiluminescence Emission Modementioning
confidence: 99%
“…Molecules 2021, 26, 7664 19 of 30 was found that Co 2+ -chitosan increased the CL emission of the system when merged with the β-CD nanoassembly system [126]. Another interesting CL system of cyclic peroxides was catalytically produced by tetrahydrofuran hydrogen peroxide in the presence of BSA-stabilized Gold Nanoclusters (Au@BSA NCs).…”
Section: Intermolecular Chemiluminescence Emission Modementioning
confidence: 99%
“…Energy transfer in a supramolecular system can be readily investigated through steady-state spectroscopic measurements. [61,62] For instance, the complexation of one equivalent of either Np14CMe 2 or Ant910H with two equivalents of CB [7] generates discrete monomers in aqueous solution (Figure 4 a; see Figure S24). [34,36] Their steady-state spectra in Figure 4 c shows that the superposition (the mathematical "mixture") of both monomers spectra (Figure 4 b) resulting in absoroption and emission profiles identical to those recorded for their 50/50 physical mixture.…”
mentioning
confidence: 99%
“…Different energy transfer mechanisms have been extensively discussed not only in physics, but also in several areas like chemistry, biology and engineering. An efficient energy transfer allows for a variety of applications, such as photovoltaics [6], luminescence [7,8], sensing [9], quantum information [10,11], and many others. Due to these numerous applications and to advances in different areas combined with the great development of new technologies, controlled modification of the RET rate has also become a topic of huge interest.…”
mentioning
confidence: 99%
“…Despite its relative simplicity, we could not solve (8) in terms of well known functions. We are, however, particularly interested in the |2iω 0 0 /σ xx | 1/z regime, corresponding to low magnetic fields (away from the abrupt changes at the LL transitions).…”
mentioning
confidence: 99%